The contact and photoconductivity characteristics between Co doped amorphous carbon and GaAs: n-type low-resistivity and semi-insulated high-resistivity GaAs. (12th May 2016) - Zhai, Zhangyin; Yu, Hualing; Zuo, Fen; Guo, Chunlian; Chen, Guibin; Zhang, Fengming; Wu, Xiaoshan; Gao, Ju
Abstract: The Co doped amorphous carbon films (a-C:Co), deposited by pulsed laser deposition, show p-n and ohmic contact characteristics with n-type low resistivity GaAs (L-GaAs) and semi-insulated high-resistivity GaAs (S-GaAs). The photosensitivity enhances for a-C:Co/L-GaAs, while inverse decreases for a-C:Co/S-GaAs heterojunction, respectively. Furthermore, the enhanced photosensitivity for the a-C:Co/L-GaAs/Ag heterojunction also shows deposition temperature dependence behavior, and the optimum deposition temperature is around 500 °C.